2000
DOI: 10.1002/1521-1878(200101)23:1<95::aid-bies1012>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Abalone lysin: the dissolving and evolving sperm protein

Abstract: Abalone sperm lysin is a non-enzymatic protein that creates a hole for sperm passage in the envelope surrounding the egg. Lysin exhibits species-specificity in making the hole and it evolves rapidly by positive selection. Our studies have focused on combining structural, biochemical, and evolutionary data to understand the mechanism of action and evolution of this remarkable protein. Currently, more is known about lysin than about any other protein involved in animal fertilization. We present an hypothesis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…For example, in abalones, a meeting of a sperm and egg begins with exocytosis of the sperm acrosome (releasing lysin) in the egg jelly coat, continues with penetration of the sperm through the egg vitelline envelope (mediated by lysin and VERL), and ends with fusion of the sperm and egg membranes (Kresge et al 2001). Progress toward fertilization may halt at any of these steps.…”
Section: Ore Locimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in abalones, a meeting of a sperm and egg begins with exocytosis of the sperm acrosome (releasing lysin) in the egg jelly coat, continues with penetration of the sperm through the egg vitelline envelope (mediated by lysin and VERL), and ends with fusion of the sperm and egg membranes (Kresge et al 2001). Progress toward fertilization may halt at any of these steps.…”
Section: Ore Locimentioning
confidence: 99%
“…Several pairs of proteins are suspected of mediating sexual conflict. For example, in abalones and sea urchins, the strength of binding between certain sperm and egg proteins affects the frequency of fertilization when a sperm and egg meet (Metz et al 1994, Palumbi 1999Kresge et al 2001); mutations in the sperm proteins may be favored if they raise the frequency of fertilization and hence of victory in sperm competition, whereas mutations in the egg proteins may be favored if they lower the frequency of fertilization and hence of death by polyspermy (Rice and Holland 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research over the past two decades has shown that these interactions govern at least some aspect of each question above. In cases such as the spawning abalone (1,2) and the disinterested female fly, (3,4) the causative proteins and molecular interactions are clear, but most reproductive phenotypes and behaviors remain unexplained at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms have been studied extensively in the abalone genus Haliotus, in which successful fertilization depends on the complex interaction between the egg protein VERL ("Vitelline Envelope Receptor for Lysin") and the sperm protein lysin (Kresge et al, 2001). Molecular analyses of these proteins revealed signatures of strong selection, indicating rapid evolution (Lee et al, 1995, Swanson andVacquier, 1998).…”
Section: (B) Temporal Isolationmentioning
confidence: 99%